CONGRUENCE OF STRATEGIES TO MANAGE CAUSES AND EFFECTS OF TEST ANXIETY AMONG INTERNATIONAL BACCALAUREATE STUDENTS BEFORE TAKING THEIR FINAL EXAMS - Danuta Główka (Pavlo Tychyna Uman State Pedagogical University, 2018)
International Baccalaureate (IB) students experience test anxiety connected with taking the high stakes final exams, following the two-year Diploma Programme Courses. The aim of this paper is to investigate the congruence of the causes and effects of test anxiety with strategies to manage this anxiety among IB students before taking their final exams. Qualitative responses about test anxiety from 21 IB students were collected before their exams. Causes of anxiety, as reported by the students, had to do with peer pressure and negative self-talk before the exams. Effects of anxiety were related to physical and emotional functioning as well as cognition. Strategies for managing anxiety included a variety of physical and intellectual activities. Comparing students' reported causes and effects of anxiety with their strategies to manage it revealed little correspondence between the causes and effects of a student's test anxiety and the kinds of strategies he or she employed to manage them.